Analisis Kebijakan Program Jaminan Kesehatan Nasional Untuk Daerah Tertinggal (Studi Kasus Kepulauan Mentawai) - Desi Fitrianeti; Ayurisya Dominata (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is to analyze the policy of the JKN program in the Mentawai Islands. This research method uses a qualitative descriptive method with data collection techniques through unstructured interviews, observation, literature studies, and review of policy documents that have existed or been implemented in central and regional government agencies that are relevant to the research topic. From the research results, it was found that the implementation of the JKN program in the Mentawai Islands until June 2022 has not been optimal due to the validity factor of membership data, the JKN services currently available are limited to the type of prolacnis patient, and there are still a total of 25,122 people (27.30%) residents of the Mentawai Islands don't have JKN yet. The research conclusions show that the government needs to increase the availability of infrastructure, tools, medicines, BHP (supply sites), human resources for health facilities, as well as easy access to capitation funds that support the implementation of the JKN program in the Mentawai Islands. Keywords: Health, Insurance, Mentawai, Policy